Evaluation of African oil palm germplasm for drought tolerance - Reddi, Sanjeevraddi G.; Patil, D.R.; Maheshwarappa, H.P.; Arulraj, S.; Reddy, B.G. Mastana; Chandravathi, B. (Journal of Plantation Crops, 2014)
A field experiment was conducted at ARS Campus, Gangavati, University of Horticultural Sciences, Bagalkot to evaluate the oil palm genotypes for drought tolerance under medium black soils of Tungabhadra Command area of Karnataka. Nine oil palm genotypes were collected from Zambia and Tanzania for drought tolerance studies under rainfed conditions. The genotype ZS-3 recorded significantly higher fresh fruit bunch (FFB) yield 7.0 t ha-1 over Z-6, ZS-8, ZS-8, ZS-9, TS-5 and TS-7. Number of bunches were significantly higher in the genotypes ZS-3 (4.4) followed by ZS-1 (4.1) and ZS-9 (4.0). Bunch weight was significantly higher in the genotype ZS-3 (11.2 kg bunch-1) followed by ZS-5 (10.8 kg bunch-1) and ZS-6 (9.4 kg bunch-1). The number of fruits per bunch was significantly higher in the genotype ZS-8 (3031) over all other genotypes. The number of male inflorescence was lower with the genotype ZS-5 and TS-5 (7.8 and 8.0 respectively). The number of female inflorescence was higher with the genotypes ZS-3 and TS-5 (7.0 and 7.0, respectively). Per cent sex ratio was higher with the genotype TS-5 and ZS-5 (46.2 and 44.8, respectively). The genotype ZS-1 and ZS-5 recorded higher annual leaf production of 21.4 and 20.3, respectively. The genotype ZS-1 recorded significantly lower number of leaf scorched per palm of 2.2 over other genotypes but it was on par with genotype ZS-3 (3.6). The data on various physiological and biochemical parameters revealed that the genotype ZS-1 and ZS-3 recorded higher relative water content, lower electrolyte leaching and significantly lower peroxidase activity indicating relatively more stress tolerant than other tested genotypes.